Polypropylene material based on nano-filling toughening technology and preparation process thereof

By using nano-toughening fillers such as nano-calcium carbonate, nano-silica and nano-montmorillonite in polypropylene materials, and using masterbatch method and reasonable formulation design, the problems of insufficient toughness of polypropylene materials and poor dispersion of nano-fillers are solved, achieving efficient toughening and performance improvement.

CN119912751APending Publication Date: 2025-05-02SUZHOU HECHANG POLYMERIC MATERIALS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510295236.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The lack of toughness of traditional polypropylene materials leads to brittle fracture easily when impacted by external forces, and the dispersion of nanofillers in the polypropylene matrix is ​​poor, affecting the uniformity of material properties.

Method used

Nanotropic fillers such as nanocalcium carbonate, nanosilica and nanomontmorillonite were used to secondary disperse nanosilica through the masterbatch method and the reasonable formulation design and mixing process optimization to improve the dispersion and compatibility of nanofillers in the polypropylene matrix.

Benefits of technology

The impact resistance of polypropylene materials is significantly improved, brittle fracture phenomenon is avoided, the overall mechanical properties and oxidation resistance of the material are enhanced, while simplifying the process and reducing costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of polypropylene material preparation, and discloses a polypropylene material based on a nano-filling toughening technology, and the polypropylene material comprises the following components by weight: 50-80 parts of polypropylene resin; 5 to 20 parts of nano toughening filler; 2-10 parts of a compatilizer; 0.1 to 1 part of an antioxidant; and 0.1-5 parts of other auxiliary agents. According to the polypropylene material based on the nano filling toughening technology, by adding nano calcium carbonate, nano silicon dioxide, nano montmorillonite and other specific nano toughening fillers and by means of the unique physical and chemical properties of a nano material, an effective toughening network structure is constructed in a polypropylene matrix, and when the material is impacted by external force, the polypropylene material can be effectively toughened. The network structure can efficiently absorb and disperse impact energy, greatly improves the impact resistance of the material, effectively avoids the brittle fracture phenomenon easily occurring in the traditional polypropylene material, and can better meet the harsh standard of related parts on the impact resistance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polypropylene material preparation, in particular to a polypropylene material based on nano-filling toughening technology and a preparation process thereof. Background Art

[0002] Polypropylene is a thermoplastic synthetic resin with excellent performance. It has been widely used in many fields such as automobile manufacturing, electronic appliances, packaging materials, and construction materials due to its advantages of low density, good mechanical properties, high chemical stability, easy processing and molding, and low price. With the development of social economy and the continuous advancement of science and technology, various industries have put forward higher requirements on the performance of polypropylene materials, especially the increasingly stringent requirements on its toughness. In practical applications, traditional polypropylene materials have some shortcomings that cannot be ignored, among which insufficient toughness is one of the key issues that restrict its further widespread application. Ordinary polypropylene materials are prone to brittle fracture when subjected to external force impact, which greatly affects its use in some occasions with high requirements for material impact resistance, such as automobile bumpers, electrical housings and other components. At present, the common methods for improving the toughness of polypropylene materials mainly include rubber toughening, elastomer toughening, etc. However, although these traditional toughening methods can improve the toughness of polypropylene to a certain extent, they will also cause the rigidity, strength and other properties of the material to decrease, and the toughening effect is limited, which cannot meet the needs of modern industry for high-performance polypropylene materials. In addition, these methods may also have problems such as complex processing technology and high cost, which limit their large-scale application. With the rapid development of nanotechnology, nanomaterials have shown great potential in the field of material modification due to their unique small size effect, surface effect and quantum size effect. The use of nanomaterials as toughening fillers in the modification of polypropylene materials is expected to improve the toughness of polypropylene while maintaining or even improving its other properties, providing new ideas and methods for solving the problem of insufficient toughness of polypropylene materials. However, there are still some urgent problems to be solved in the application of nano-filling toughening technology in polypropylene materials. For example, the dispersion of nanofillers in the polypropylene matrix is ​​poor and they are prone to agglomeration. This not only fails to fully exert the toughening effect of nanofillers, but also leads to uneven material properties and affects the overall performance of the material. Therefore, it is of great practical significance and application value to develop a technology that can effectively improve the dispersion of nanofillers in the polypropylene matrix and thereby enhance the mechanical properties of polypropylene materials. Summary of the invention

[0003] The purpose of the present invention is to provide a polypropylene material based on nano-filling toughening technology and a preparation process thereof, so as to solve the problems of insufficient toughness of traditional polypropylene materials and poor dispersion of nano-fillers mentioned in the above background technology.

[0004] To achieve the above object, the present invention provides the following technical solution: a polypropylene material based on nano-filling toughening technology, the polypropylene material comprises the following components by weight: Polypropylene resin 50-80 parts; 5-20 parts of nano toughening filler; Compatibilizer 2-10 parts; Antioxidant 0.1-1 part; Other additives 0.1-5 parts.

[0005] Preferably, the nano toughening filler is one of nano calcium carbonate, nano silicon dioxide and nano montmorillonite.

[0006] Preferably, the compatibilizer is one or more combinations of maleic anhydride grafted polypropylene, ethylene-acrylic acid copolymer, and ethylene-acrylate-maleic anhydride copolymer.

[0007] Preferably, the antioxidant is a combination of one or more hindered phenol antioxidants and phosphite antioxidants.

[0008] Preferably, the other additives include one or more combinations of lubricants, light stabilizers, and flame retardants; The lubricant is one of ethylene bis stearamide and zinc stearate; The light stabilizer is a hindered amine light stabilizer; The flame retardant is one of decabromodiphenylethane and triphenyl phosphate.

[0009] A preparation process of a polypropylene material based on nano-filling toughening technology, the preparation process comprising the following steps: S1. Weigh each component according to the formula; S2. When nano-silicon dioxide is used as a nano-toughening filler, the masterbatch method is used to secondary disperse the nano-silicon dioxide to improve its dispersibility in the composite material, so as to enhance the mechanical properties of the composite material. The remaining polypropylene resin, nano-silicon dioxide masterbatch, compatibilizer, antioxidant and other additives are added to a high-speed mixer. When nano-calcium carbonate or nano-montmorillonite is used as a nano-toughening filler, the polypropylene resin, nano-toughening filler, compatibilizer, antioxidant and other additives are directly added to the high-speed mixer; S3, the materials are mixed in a high-speed mixer at 80-120° C. for 10-30 min to obtain a premix; S4, adding the premix into a twin-screw extruder, and performing melt blending and extrusion at a temperature range of 180-240°C. The extrudate is cooled and pelletized to obtain a polypropylene material based on nano-filling toughening technology. Preferably, the specific operation steps of secondary dispersing nano silicon dioxide by the masterbatch method in S2 are as follows: T1. First, add 10-30 parts of polypropylene resin and 5-15 parts of nano-silicon dioxide into a high-speed mixer, and add 1-5 parts of a compatibilizer at the same time; T2, setting the stirring speed of the high-speed stirrer to 800-1500 rpm, mixing at 80-120° C. for 15-25 min to prepare a nano-silicon dioxide masterbatch; T3. After the mixing is completed, the obtained nano-silicon dioxide masterbatch is taken out for later use.

[0010] Preferably, the screw speed of the twin-screw extruder is 200-500 rpm.

[0011] Preferably, during the melt blending extrusion process, the temperature of each section of the twin-screw extruder is set to: 180-200°C for the feeding section, 200-220°C for the melting section, 220-240°C for the mixing section, 220-240°C for the homogenizing section, and 220-240°C for the head section.

[0012] Compared with the prior art, the invention has the following beneficial effects: the polypropylene material based on nano-filling toughening technology: 1. By adding specific nano-toughening fillers such as nano-calcium carbonate, nano-silicon dioxide and nano-montmorillonite, an effective toughening network structure is constructed in the polypropylene matrix by virtue of the unique physical and chemical properties of nano-materials. When the material is subjected to external impact, the network structure can efficiently absorb and disperse the impact energy, greatly improving the impact resistance of the material and effectively avoiding the brittle fracture phenomenon that is prone to occur in traditional polypropylene materials. This enables the polypropylene material of the present invention to better meet the stringent standards of the relevant components for the material impact resistance in applications in high-demand fields such as automobile manufacturing and electronic appliances, and significantly improve the quality and safety of the product; 2. In order to solve the problem of poor dispersion of nanofillers in polypropylene matrix, when using nanosilica as toughening filler, the masterbatch method is used to disperse nanosilica for the second time. First, the nanosilica masterbatch is prepared and then mixed with other components, which greatly improves the uniformity of nanosilica dispersion in the composite material. When using nano-calcium carbonate or nano-montmorillonite, the uniform dispersion of nanofillers in the polypropylene matrix is ​​ensured through reasonable formula design and optimization of mixing process parameters. This not only gives full play to the toughening effect of nanofillers, but also enhances the overall mechanical properties of the composite material, making the material performance more stable and reliable. 3. Through the reasonable selection and dosage control of compatibilizers, antioxidants and other additives, the present invention effectively improves the compatibility between the nanofiller and the polypropylene matrix, so that the nanofiller can be better combined with the polypropylene matrix and work synergistically. At the same time, this optimization also significantly improves the antioxidant properties of the material, prolongs the service life of the material, and improves the processing performance of the material, making it easier to shape and process during the production process, reducing the defective rate and production cost, and ensuring the stability and reliability of the material under different environmental conditions, thereby expanding the application range of the material; 4. The preparation process of the present invention is simple to operate, does not require complicated equipment and technology, is easy to master and implement, and at the same time, the process cost is controllable. In the selection of raw materials and the production process, reasonable formula design and process optimization are used to reduce production costs and improve production efficiency. This makes the technology very suitable for large-scale industrial production and can provide the market with sufficient high-performance polypropylene materials to meet the large demand for this material in various industries. DETAILED DESCRIPTION

[0013] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0014] The invention provides a technical solution: a polypropylene material based on nano-filling toughening technology.

[0015] Embodiment 1: Raw material formula (by weight): Polypropylene resin: 60 parts Nano toughening filler (nano calcium carbonate): 10 parts Compatibilizer (maleic anhydride grafted polypropylene): 5 parts Antioxidant (hindered phenol antioxidant): 0.5 parts Other additives (lubricant ethylene bis stearamide 2 parts, light stabilizer hindered amine light stabilizer 1 part, flame retardant decabromodiphenyl ethane 1 part): 4 parts Preparation steps: S1: Weigh each component according to the above formula.

[0016] S2: Add polypropylene resin, nano calcium carbonate, maleic anhydride grafted polypropylene, hindered phenol antioxidant and other additives into a high-speed mixer.

[0017] S3: The materials were mixed in a high-speed mixer at 100° C. for 20 min to obtain a premix.

[0018] S4: adding the premix into a twin-screw extruder, setting the temperature of each section of the twin-screw extruder to: 190°C for feeding section, 210°C for melting section, 230°C for mixing section, 230°C for homogenizing section, 230°C for head section, and 300rpm for screw speed, performing melt blending and extrusion within this temperature range, cooling and pelletizing the extrudate to obtain a polypropylene material based on nano-filling toughening technology.

[0019] Performance testing: Impact strength: According to the ISO180-2019 "Determination of Izod Impact Properties of Plastics" standard, standard specimens were made and tested on a cantilever beam impact testing machine. The results showed that its impact strength was 40% higher than that of traditional polypropylene materials.

[0020] Tensile strength: According to GB / T1040.2-2006 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics", a tensile test was conducted on a dumbbell-shaped standard specimen on a universal material testing machine, and the tensile strength was measured to be increased by 15%.

[0021] Bending strength: According to GB / T9341-2008 "Determination of Flexural Properties of Plastics" standard, the three-point bending test method was used on a universal material testing machine, and the bending strength performance was good.

[0022] Antioxidant properties: TGA and DSC tests showed that the thermal decomposition starting temperature of the material was high, the oxidation induction period was long, and the antioxidant properties were good.

[0023] Processing performance: According to GB / T3682.1-2018 "Plastics Thermoplastics - Determination of Melt Mass Flow Rate (MFR) and Melt Volume Flow Rate (MVR) Part 1: Standard Method", the material was tested on a melt flow rate meter and showed good processing performance.

[0024] Embodiment 2: Raw material formula (by weight): Polypropylene resin: 70 parts Nano toughening filler (nano silica): 12 parts Compatibilizer (ethylene-acrylic acid copolymer): 6 parts Antioxidant (phosphite antioxidant): 0.6 parts Other additives (lubricant zinc stearate 1 part, light stabilizer hindered amine light stabilizer 1 part, flame retardant triphenyl phosphate 2 parts): 4 parts Preparation steps: T1: First, add 20 parts of polypropylene resin and 8 parts of nano-silicon dioxide into a high-speed mixer, and at the same time add 3 parts of ethylene-acrylic acid copolymer.

[0025] T2: The stirring speed of the high-speed stirrer was set to 1000 rpm, and the mixture was mixed at 100° C. for 20 min to prepare a nano-silica masterbatch.

[0026] T3: After the mixing is completed, the obtained nano-silica masterbatch is taken out for later use.

[0027] S1: weigh the remaining polypropylene resin, nano-silica masterbatch, the remaining ethylene-acrylic acid copolymer, phosphite antioxidant and other additives according to the formula.

[0028] S2: Add the above materials into a high-speed mixer.

[0029] S3: The materials were mixed in a high-speed mixer at 100° C. for 20 min to obtain a premix.

[0030] S4: adding the premix into a twin-screw extruder, setting the temperature of each section of the twin-screw extruder as follows: 190°C for feeding section, 210°C for melting section, 230°C for mixing section, 230°C for homogenizing section, 230°C for head section, and a screw speed of 350rpm. Melt blending and extrusion are carried out within this temperature range. The extrudate is cooled and pelletized to obtain a polypropylene material based on nano-filling toughening technology.

[0031] Performance testing: Impact strength: According to the ISO180-2019 "Determination of Izod Impact Properties of Plastics" standard, standard specimens were made and tested on a cantilever beam impact testing machine. The results showed that its impact strength was 45% higher than that of traditional polypropylene materials.

[0032] Tensile strength: According to GB / T1040.2-2006 standard, the tensile test was carried out on the dumbbell-shaped standard specimen on the universal material testing machine, and the tensile strength was measured to be increased by 20%.

[0033] Bending strength: According to GB / T9341-2008 standard, the three-point bending test method was used on a universal material testing machine, and the bending strength performance was good.

[0034] Antioxidant properties: The results of TGA and DSC tests showed that the thermal decomposition starting temperature of the material was high, the oxidation induction period was long, and the antioxidant properties were excellent.

[0035] Processing performance: According to GB / T3682.1-2018 standard, the material was tested on a melt flow rate meter. The melt flow rate of the material is good and the processing performance is excellent.

[0036] Embodiment 3: Raw material formula (by weight): Polypropylene resin: 55 parts Nano toughening filler (nano montmorillonite): 8 parts Compatibilizer (ethylene-acrylate-maleic anhydride copolymer): 4 parts Antioxidant (0.3 parts each of hindered phenol antioxidant and phosphite antioxidant): 0.6 parts Other additives (lubricant ethylene bis stearamide 1.5 parts, light stabilizer hindered amine light stabilizer 1 part, flame retardant decabromodiphenyl ethane 1.5 parts): 4 parts Preparation steps: S1: Weigh each component according to the above formula.

[0037] S2: Add polypropylene resin, nano-montmorillonite, ethylene-acrylate-maleic anhydride copolymer, hindered phenol antioxidant, phosphite antioxidant and other additives into a high-speed mixer.

[0038] S3: The materials are mixed in a high-speed mixer at 90° C. for 25 min to obtain a premix.

[0039] S4: adding the premix into a twin-screw extruder, setting the temperature of each section of the twin-screw extruder as follows: 185°C for feeding section, 205°C for melting section, 225°C for mixing section, 225°C for homogenizing section, 225°C for head section, and a screw speed of 250rpm. Melt blending and extrusion are carried out within this temperature range. The extrudate is cooled and pelletized to obtain a polypropylene material based on nano-filling toughening technology.

[0040] Performance testing: Impact strength: According to ISO180-2019 standard, standard specimens were made and tested on a cantilever beam impact testing machine. The measured impact strength was 35% higher than that of traditional polypropylene materials.

[0041] Tensile strength: According to GB / T1040.2-2006 standard, tensile test was carried out on dumbbell-shaped standard specimens on a universal material testing machine, and the tensile strength met the requirements.

[0042] Bending strength: According to GB / T9341-2008 standard, the three-point bending test method was used on a universal material testing machine, and the bending strength was in line with expectations.

[0043] Antioxidant properties: Through TGA and DSC tests, the material has a high thermal decomposition starting temperature, a long oxidation induction period, and good antioxidant properties.

[0044] Processing performance: According to GB / T3682.1-2018 standard, tested on a melt flow rate meter, the processing performance of the material can meet the needs of various industrial applications.

[0045] The above specific embodiments further illustrate the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific embodiments of the present invention and do not limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are included in the protection scope of the present invention.

Claims

1. A polypropylene material based on nano-filling toughening technology, characterized in that: The polypropylene material comprises the following components by weight: Polypropylene resin 50-80 parts; 5-20 parts of nano toughening filler; Compatibilizer 2-10 parts; Antioxidant 0.1-1 part; Other additives 0.1-5 parts.

2. The polypropylene material based on nano-filling toughening technology according to claim 1, characterized in that: The nano toughening filler is one of nano calcium carbonate, nano silicon dioxide and nano montmorillonite.

3. The polypropylene material based on nano-filling toughening technology according to claim 1, characterized in that: The compatibilizer is one or more combinations of maleic anhydride grafted polypropylene, ethylene-acrylic acid copolymer, and ethylene-acrylate-maleic anhydride copolymer.

4. The polypropylene material based on nano-filling toughening technology according to claim 1, characterized in that: The antioxidant is one or more combinations of hindered phenol antioxidants and phosphite antioxidants.

5. The polypropylene material based on nano-filling toughening technology according to claim 1, characterized in that: The other additives include one or more combinations of lubricants, light stabilizers, and flame retardants; The lubricant is one of ethylene bis stearamide and zinc stearate; The light stabilizer is a hindered amine light stabilizer; The flame retardant is one of decabromodiphenylethane and triphenyl phosphate.

6. The process for preparing a polypropylene material based on nano-filling toughening technology according to any one of claims 1 to 5, characterized in that: The preparation process comprises the following steps: S1. Weigh each component according to the formula; S2. When nano-silicon dioxide is used as a nano-toughening filler, the masterbatch method is used to secondary disperse the nano-silicon dioxide to improve its dispersibility in the composite material, so as to enhance the mechanical properties of the composite material. The remaining polypropylene resin, nano-silicon dioxide masterbatch, compatibilizer, antioxidant and other additives are added to a high-speed mixer. When nano-calcium carbonate or nano-montmorillonite is used as a nano-toughening filler, the polypropylene resin, nano-toughening filler, compatibilizer, antioxidant and other additives are directly added to the high-speed mixer; S3, the materials are mixed in a high-speed mixer at 80-120° C. for 10-30 min to obtain a premix; S4. Add the premix into a twin-screw extruder, perform melt blending and extrusion at a temperature range of 180-240° C., cool and pelletize the extrudate to obtain a polypropylene material based on nano-filling toughening technology.

7. The process for preparing a polypropylene material based on nano-filling toughening technology according to claim 6, characterized in that: The specific operation steps of secondary dispersion of nano silicon dioxide by the masterbatch method in S2 are as follows: T1. First, add 10-30 parts of polypropylene resin and 5-15 parts of nano-silicon dioxide into a high-speed mixer, and add 1-5 parts of a compatibilizer at the same time; T2, setting the stirring speed of the high-speed stirrer to 800-1500 rpm, mixing at 80-120° C. for 15-25 min to prepare a nano-silicon dioxide masterbatch; T3. After the mixing is completed, the obtained nano-silicon dioxide masterbatch is taken out for later use.

8. The process for preparing a polypropylene material based on nano-filling toughening technology according to claim 6, characterized in that: The screw speed of the twin-screw extruder is 200-500 rpm.

9. The process for preparing a polypropylene material based on nano-filling toughening technology according to claim 6, characterized in that: During the melt blending extrusion process, the temperature of each section of the twin-screw extruder is set to: 180-200°C for the feeding section, 200-220°C for the melting section, 220-240°C for the mixing section, 220-240°C for the homogenizing section, and 220-240°C for the head section.

Citation Information

Cited By

  • Calcium carbonate-based agglomerated stone filler and preparation method thereof

    CN120888119A